Nickel‐Catalyzed One‐Pot Suzuki–Miyaura Cross‐Coupling of Phenols and Arylboronic Acids Mediated by N, N‐Ditosylaniline. Issue 23 (8th July 2014) - Chen, Liangshun; Lang, Hongyue; Fang, Lei; Zhu, Mengyun; Liu, Jinqian; Yu, Jianjun; Wang, Limin
Abstract: An efficient method for the construction of two distinct Caryl –Caryl bonds through the Ni‐catalyzed Suzuki–Miyaura cross‐coupling of phenols with arylboronic acids has been developed. This reaction proceeds through the in situ tosylation of phenols by using N, N ‐ditosylaniline as the sulfonylating reagent, which is highly active, markedly stable, and easily prepared. The scope with respect to the coupling partners – phenols and boronic acids – is broad, and sensitive functional groups are tolerated. Phenols, especially those containing an unprotected amino group, which are generally problematic for coupling under conventional one‐pot conditions, are also viable substrates in this transformation. Abstract : N, N ‐Ditosylaniline is extensively investigated for the first time in the one‐pot Suzuki–Miyaura cross‐coupling of phenols with arylboronic acids. High chemical selectivity is observed between the phenols and amines, and the desired biphenyl products containing a free amino group are obtained in good yields. dppp = 1, 3‐bis(diphenylphosphino)propane.